Improving inpatient postnatal services: midwives views and perspectives of engagement in a quality improvement initiative - Wray Julie; Weavers Annette; Rose Val; Bick Debra E; Beake Sarah (BMC, 2011)
Abstract Background Despite major policy initiatives in the United Kingdom to enhance women's experiences of maternity care, improving in-patient postnatal care remains a low priority, although it is an aspect of care consistently rated as poor by women. As part of a systems and process approach to improving care at one maternity unit in the South of England, the views and perspectives of midwives responsible for implementing change were sought. Methods A Continuous Quality Improvement (CQI) approach was adopted to support a systems and process change to in-patient care and care on transfer home in a large district general hospital with around 6000 births a year. The CQI approach included an initial assessment to identify where revisions to routine systems and processes were required, developing, implementing and evaluating revisions to the content and documentation of care in hospital and on transfer home, and training workshops for midwives and other maternity staff responsible for implementing changes. To assess midwifery views of the quality improvement process and their engagement with this, questionnaires were sent to those who had participated at the outset. Results Questionnaires were received from 68 (46%) of the estimated 149 midwives eligible to complete the questionnaire. All midwives were aware of the revisions introduced, and two-thirds felt these were more appropriate to meet the women's physical and emotional health, information and support needs. Some midwives considered that the introduction of new maternal postnatal records increased their workload, mainly as a consequence of colleagues not completing documentation as required. Conclusions This was the first UK study to undertake a review of in-patient postnatal services. Involvement of midwives at the outset was essential to the success of the initiative. Midwives play a lead role in the planning and organisation of in-patient postnatal care and it was important to obtain their feedback on whether revisions were pragmatic and achieved anticipated improvements in care quality. Their initial involvement ensured priority areas for change were identified and implemented. Their subsequent feedback highlighted further important areas to address as part of CQI to ensure best quality care continues to be implemented. Our findings could support other maternity service organisations to optimise in-patient postnatal services.